Perspective for the use of adoption theories in artificial intelligence - Martins, R. do V. (2022)
The evolution of diffusion and adoption theories models took place during the last half of 20th century. Despite the longevity they are still used today, and the use was increasing in the last years, reflecting its importance as valid tools to understand the complexity of technology adoption phenomenon. During the last twenty years, one of the areas in the field of information technologies that re-emerged with a most advanced development, was artificial intelligence. This study aims to identify what is the state-of-the-art on adoption theories of information technologies at individual level, and what challenges comes from artificial intelligence that could stress the conventional adoption theories. Finally, a new work is described as a proposal to overcome these challenges.